IMMUNOMORPHOLOGICAL FEATURES OF THE HISTOLOGICAL STRUCTURES OF THE SPLEEN OF WHITE RATS IN SE MICROELEMENTOSIS - Turdiyev M.R (THE PLACE AND ROLE OF TURKEY AND THE NEAR REGION IN THE PROCESSES OF SCIENTIFIC, SOCIAL, AND CULTURAL DEVELOPMENT, 2025)
Research the breed of white rats in the period of 6 and 9 months of age without talog'i the histological structure of the tissue, the cell culture composition and immunogistokimyoviy indicators were analyzed. That results in the failure analysis of selenium alimentar parenxima this member-strong balance the violation of limfoid tissue morfometrik indicators, limfoid and will determine the level of reduction in the number of cells express immunogistokimyoviy markyorlar. These changes decrease the body's immune response suppression and protection with appeared.